2011
DOI: 10.1159/000330601
|View full text |Cite
|
Sign up to set email alerts
|

Increased Matrix Metalloproteinase-2 and Bone Sialoprotein Response to Human Coronal Caries

Abstract: Background: It has been suggested that host matrix metalloproteinase-2 (MMP-2) present in dentin may be involved in caries progression, however, its response to caries is not known. Bone sialoprotein (BSP) has been implicated in dentin mineralization and MMP-2 modulation. Objective: To identify and compare the distribution of MMP-2 and BSP in healthy human coronal dentin and those with early caries. Methods: Freshly extracted 3rd molars and premolars with and without early caries were fixed, demineralized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…Although the expression of MMP-2 and MMP-9 was not statistically different between the baseline and 60-day sample, we cannot rule out the fact that their expression was still high compared to that of sound teeth. This hypothesis can be reinforced by the observation that immunoreactivity for these MMPs in sound dentin was only shown to be present in predentin and the enamel-dentin junction [Boushell et al, 2011], but not around dentin tubules as detected in this study.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Although the expression of MMP-2 and MMP-9 was not statistically different between the baseline and 60-day sample, we cannot rule out the fact that their expression was still high compared to that of sound teeth. This hypothesis can be reinforced by the observation that immunoreactivity for these MMPs in sound dentin was only shown to be present in predentin and the enamel-dentin junction [Boushell et al, 2011], but not around dentin tubules as detected in this study.…”
Section: Discussionsupporting
confidence: 71%
“…The evident labeling of MMP-2 surrounding dentin tubules may be related to MMP-2 newly secreted by odontoblasts as a reparative reaction, a finding already demonstrated in early studies of dentin caries [Toledano et al, 2010;Boushell et al, 2011]. Thus, the weak detection of MMP-2 in the intertubular dentin may be due to the short evaluation period after cavity sealing, which was probably not enough to allow diffusion of the newly secreted MMP-2 to the intertubular dentin.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Caries stimulates MMP-2 expression in human odontoblasts in vivo (Charadram et al 2012). MMP-2 seems to be actively secreted by odontoblasts in response to carious insult (Boushell et al 2011), resulting in the differential expression of this protease in sound, caries-affected, and caries-infected dentin (Toledano et al 2010;Charadram et al 2012). Increased levels of MMP-9 (Zehnder et al 2011) and MMP-20 (Sulkala et al 2002) in dentinal tubules under caries lesions have also been demonstrated.…”
Section: Dental Caries and Role Of Mmps In Caries Progressionmentioning
confidence: 98%
“…More recently, MMPs were identified as being responsible for that activity (Tjäderhane et al 1998), and to date, the presence of gelatinases MMP-2 and -9 ( Fig. 1), collagenase MMP-8, stromelysin MMP-3, and MMP-20 have been reported (Martin-De Las Heras et al 2000;Sulkala et al 2002;Mazzoni et al 2007;Sulkala et al 2007;Boukpessi et al 2008;Mazzoni et al 2009;Santos et al 2009;Boushell et al 2011;.…”
mentioning
confidence: 94%